Cosmology, Community, and Continuity: Hindu Kaharingan and the Future of Sustainable Civilization - Agung Adi; Ervantia Restulita L. Sigai; Heri Kusuma Tarupay; Stepenson Stepenson (IAHN-TP Palangka Raya, 2026)
This study stems from a critique of the global development paradigm, which tends to be reductionist in its understanding of sustainability by separating ecological, social, and cultural dimensions. This article argues that Hindu Kaharingan, as the religio-cultural system of the Dayak people, offers an integrative alternative model through the interconnection of cosmology, community, and continuity as the foundation of a sustainable civilization. Using a critical-interpretive qualitative approach, this study analyzes Kaharingan cosmology as a relational ontology, community practices as the basis for social sustainability, and the dynamics of continuity as a form of living heritage. The findings indicate that Hindu Kaharingan not only contains ecological ethics but also social and cultural mechanisms that support holistic sustainability. However, this integration faces tensions with a global paradigm that is fragmentary, technocratic, and tends to instrumentalize local knowledge. The novelty of this research lies in the development of an integrative sustainability framework grounded in religio-cultural principles that not only describes local values but also critiques power relations within global discourses. Thus, Hindu Kaharingan is positioned as a relevant epistemic resource in building a more reflective, relational, and contextual sustainable civilization.